2019
DOI: 10.1101/mcs.a003681
|View full text |Cite
|
Sign up to set email alerts
|

Base excision repair deficiency signatures implicate germline and somatic MUTYH aberrations in pancreatic ductal adenocarcinoma and breast cancer oncogenesis

Abstract: We report a case of early-onset pancreatic ductal adenocarcinoma in a patient harboring biallelic MUTYH germline mutations, whose tumor featured somatic mutational signatures consistent with defective MUTYH -mediated base excision repair and the associated driver KRAS transversion mutation p.Gly12Cys. Analysis of an additional 730 advanced cancer cases ( N = 731) was undertaken to determine whether the mutational signat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 43 publications
0
28
1
Order By: Relevance
“…Although the significance of germline variants in BRIP1 , CHEK2 , and monoallelic MUTYH within the context of PDAC remains uncertain, the implications with regard to other hereditary cancer risks remain clinically meaningful and demonstrate the utility of wider gene panel testing. Furthermore, these findings could have potential future relevance as an increased understanding of their contribution to various cancers evolve . A recent study on 289 resected PDAC cases unselected for personal or family history characteristics with a 9.7% germline mutation rate using a 24 gene panel showed that fewer than half of the germline cases had an identified second hit in the wild‐type allele of the tumor by paired somatic analysis .…”
Section: Discussionmentioning
confidence: 95%
“…Although the significance of germline variants in BRIP1 , CHEK2 , and monoallelic MUTYH within the context of PDAC remains uncertain, the implications with regard to other hereditary cancer risks remain clinically meaningful and demonstrate the utility of wider gene panel testing. Furthermore, these findings could have potential future relevance as an increased understanding of their contribution to various cancers evolve . A recent study on 289 resected PDAC cases unselected for personal or family history characteristics with a 9.7% germline mutation rate using a 24 gene panel showed that fewer than half of the germline cases had an identified second hit in the wild‐type allele of the tumor by paired somatic analysis .…”
Section: Discussionmentioning
confidence: 95%
“…Founder mutations in common cancer predisposition genes such as BRCA1 , BRCA2 , CHEK2 , and MUTYH should be excluded from global allele frequency thresholds used in automated variant filtering. For example, more than 1% of patients in the POG program are carriers for pathogenic MUTYH variants, reflecting a strong representation of individuals of East and Southeast Asian descent in BC ( 9 , 18 ). In such cases, we recommend developing highly curated internal databases with known pathogenic and likely pathogenic germline variants to reduce the incidence of false-negative findings.…”
Section: Germline Variant Curation Validation and Returnmentioning
confidence: 99%
“…For individuals with phenotypic indications of high-penetrance cancer predisposition syndromes and uninformative clinical genetic testing, evaluation of tumor WGS and RNA sequencing may improve genetic diagnosis through the resolution of potential splicing variants, noncoding variants in regulatory regions, or structural variants ( 9 , 19 ). Tumor data may also inform possible roles for VUS or autosomal recessive gene variants in pathogenesis, recently demonstrated in a patient with biallelic variants in MUTYH (p.Gly286Glu and p.Ser346Ser) with tumor evidence supporting global deficiency in base excision repair ( 7–9 ).…”
Section: Germline Variant Curation Validation and Returnmentioning
confidence: 99%
“…Pancreatic cancer is the 2 nd most common cause of cancerrelated death, despite only being the 20th most common cancer diagnosis. With the highest mortality rate among all major cancers, 5-year survival rates (Stage I~13%, Stage II~6% , Stage III~3%, Stage IV~2%) have not improved significantly over the past decade (1-3), even though extensive research efforts have uncovered new risk factors (4-9), genetic mutations (8,(10)(11)(12)(13)(14)(15)(16)(17)(18) and therapeutic options (19)(20)(21)(22)(23)(24)(25)(26). Pancreatic cancer is generally a disease of older patients that is characterized by late diagnosis, rapid disease progression and resistance to chemotherapeutic treatments (1,3).…”
mentioning
confidence: 99%